The effects of aspirin on platelet function and lysophosphatidic acids depend on plasma concentrations of EPA and DHA. (May 2015) - Block, Robert C.; Abdolahi, Amir; Tu, Xin; Georas, Steve N.; Brenna, J. Thomas; Phipps, Richard P.; Lawrence, Peter; Mousa, Shaker A.
Abstract: Aspirin׳s prevention of cardiovascular disease (CVD) events in individuals with type 2 diabetes mellitus is controversial. Eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) and aspirin all affect the cyclooxygenase enzyme. The relationship between plasma EPA and DHA and aspirin׳s effects has not been determined. Thirty adults with type 2 diabetes mellitus ingested aspirin (81 mg/day) for 7 days, then EPA+DHA (2.6 g/day) for 28 days, then both for another 7 days. Lysophosphatidic acid (LPA) species and more classic platelet function outcomes were determined. Plasma concentrations of total EPA+DHA were associated with 7-day aspirin reduction effects on these outcomes in a "V"-shaped manner for all 11 LPA species and ADP-induced platelet aggregation. This EPA+DHA concentration was quite consistent for each of the LPA species and ADP. These results support aspirin effects on lysolipid metabolism and platelet aggregation depending on plasma EPA+DHA concentrations in individuals with a disturbed lipid milieu.